Investigation of the rheological properties of low-density polyethylene (LDPE) modified bitumens using two plastic wastes - Bektas Atici, Iremgul; Yalcin, Erkut; Yilmaz, Mehmet (Yildiz Technical Univ, 2023)
This study aimed to solve one of the most significant environmental problems and develop the performance properties of bitumen using low-cost materials by utilizing low-density polyethylene (LDPE), one of the plastic wastes. Rheological characteristics of the pure binders and the LDPE modified bitumen prepared using these binders were determined at various temperatures and frequencies. In the study, modified bitumens were prepared by adding 2 different LDPEs in 4 different ratios (1%, 2%, 3%, and 4%) to the binder. The dynamic shear rheometer tests were conducted to examine the rutting resistance parameters and phase angles to examine the elastic treatment of the binders and their performance at high temperatures. Moreover, the rheological behaviors of the bituminous binders under different conditions were evaluated by testing pure and modified bitumens at 4 different temperatures and 10 different frequencies. According to the results of the analyses, the increase in the temperature led to a logarithmic decline in the rutting resistance parameters. The binders' black diagrams revealed that the modified binders prepared using LDPE A demonstrated more elastic behavior compared to the modified binders prepared using LDPE B.
Keywords: Bitumen; LDPE; Rheology; Modification